Applications of scanning electron microscopy in taxonomy with special reference to family Euphorbiaceae. Issue 9 (9th June 2020) - Alyas, Tahira; Shaheen, Shabnum; Amber, Uswah; Harun, Nidaa; Khalid, Sana; Hussain, Khadim; Hanif, Uzma; Khan, Farah
Abstract: The present study was carried out to identify the 20 medicinally important species of family Euphorbiaceae by the aid of scanning electron microscopy (SEM) of the foliar anatomical characteristics. Both qualitative and quantitative measurements for the anatomical characters like epidermal cells, stomata, trichomes, and subsidiary cells on both abaxial(ab) and adaxial(ad) epidermis were recorded. Remarkable variations in these anatomical features had been observed among the studied Euphorbiaceae species. Most species had epidermal cells irregular or polygonal in shape, only five species had hexagonal cells, that is, Euphorbia neriifolia L., Euphorbia prostate Aiton, Jatropha integerrima Jacq., Vernicia fordii (Hemsl.), and Euphorbia royleana Boiss. Stomata were abundant on abaxial epidermis as compared to adaxial epidermis. E. prostate Aiton, Euphorbia pulcherrima Willd. Ex Klotzsch and Phyllanthus emblica L. possessed anomocytic stomata, and Euphorbia helioscopia L., Euphorbia cotinifolia L., E. neriifolia L., and Ricinus communis L. possessed anisocytic stomata, while rest of the species had paracytic stomata. Trichomes were present in very few species including Euphorbia hirta L., E. prostate Aiton, E. pulcherrima Willd. Ex Klotzsch, and Putranjiva roxburghii Wall. Similarly, variations were also reported by quantitative features such as E. helioscopia L. can be distinguished from E. hirta on the basis of length of epidermal cells, that is, 103.4 ± 0.15 and 74.9 ± 0.55 μm, respectively. Moreover, E. pulcherrima Willd. Ex Klotzsch had trichomes with the length of 408 ± 0.55 μm and P. roxburghii Wall. had trichome with the length of 314.2 ± 1.35 μm, respectively. These findings confirmed that taxonomic utility of the anatomical traits for the identification of studied Euphorbiaceae taxa. Abstract : This research work mainly highlights the significance of scanning electron microscopy while studying foliar anatomical characteristics of Euphorbiaceae as it can further be used for the purpose of taxonomic identification.